PERAN GURU DALAM KOMUNIKASI EFEKTIF MELALUI KOMUNITAS BELAJAR - Fauzan, Rizki; Noor Miyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the role of teachers in fostering effective communication through teacher learning communities at SMA Negeri 1 Moga and its impact on the quality of learning. The study employed a descriptive qualitative method, with data collected through in-depth interviews, observations, and documentation. The findings revealed that effective communication within learning communities plays a crucial role in supporting instructional innovation, solving learning problems, and enhancing teachers' professional development. Teachers are able to implement more innovative teaching methods, such as project-based learning and the use of technology. Regular reflection and evaluation within the learning communities also assist teachers in improving teaching quality by identifying challenges and planning targeted follow-up actions. The conclusion of this study is that effective communication within learning communities not only enhances the quality of learning but also strengthens collaboration and teachers’ professional competencies. The implications of this study suggest the need for strengthening learning communities in schools to facilitate more effective communication among teachers, ultimately positively impacting students' learning processes.